Intervention to strengthen caregiving capacities among rural caregivers: a replicable model - Lombo-Caicedo, Jadith Cristina; Durán-Sabogal, Rosa Margarita; Palacio-Abello, Juan Domingo; Lamus-Lemus, Francisco (Frontiers in Medicine, 2025)
IntroductionDecades of armed conflict in Colombia have deeply undermined public trust in the health system, particularly within rural regions. The legacy of violence has restricted healthcare delivery in these areas, concentrating services in urban centers and exacerbating geographic and social inequities. Informal caregivers in rural communities, essential yet often overlooked actors in healthcare, face significant challenges due to structural limitations and lack of institutional support.ObjectiveThis study evaluates a community-based intervention aimed at strengthening the competencies of informal caregivers in rural, post-conflict settings. It further positions caregivers as pivotal contributors to distributed health education models, where care practices must adapt to contextual barriers and local realities.MethodsDeveloped using a Participatory Action Research (PAR) approach, the intervention engaged caregivers as co-creators. Drawing from popular education principles, it combined in-person sessions with experiential, culturally relevant materials tailored to rural environments. Ongoing remote support was provided via calls, text messages, and voice notes. The program was evaluated qualitatively through a focus group and 15 semi-structured interviews, analyzed thematically.ResultsFindings revealed four key domains of change: (1) transformation of the caregiving role, (2) personal and technical impact on caregivers, (3) shifts in family dynamics, and (4) recognition of the course as an empowering, community-building experience. Despite barriers such as digital illiteracy, poverty, and low educational attainment, participants demonstrated increased self-efficacy and engagement.ConclusionThe intervention illustrates the potential of distributed education to reduce rural health inequities. It highlights the power of academic-community partnerships in developing scalable, context-sensitive strategies that strengthen care, foster empowerment, and promote equity in underserved areas.